Mapping the contact area of the patellofemoral joint: the relationship between stability and joint congruence. (May 2019) - Clark, D.; Stevens, J. M.; Tortonese, D.; Whitehouse, M. R.; Simpson, D.; Eldridge, J.
Abstract : Aims: The aim of this study was to determine and compare the congruency of the articular surface contact area of the patellofemoral joint (PFJ) during both active and passive movement of the knee with the use of an MRI mapping technique in both the stable and unstable PFJ. Patients and Methods: A prospective case-control MRI imaging study of patients with a history of PFJ instability and a control group of volunteers without knee symptoms was performed. The PFJs were imaged with the use of an MRI scan during both passive and active movement from 0° through to 40° of flexion. The congruency through measurement of the contact surface area was mapped in 5-mm intervals on axial slices. In all, 40 patients were studied. The case group included 31 patients with symptomatic patellofemoral instability and the control group of nine asymptomatic volunteers. The ages were well matched between the case and control groups. The mean age was 25 years (16 to 42;sd 6.9) in the case group and 26 years (19 to 32;sd 5.1) in the control group. There were 19 female and 12 male patients in the case group. Results: The unstable PFJs were demonstrably less congruent than the stable PFJs throughout the range of knee movement. The greatest mean differences in congruency between unstable and stable PFJ's were observed between 11° and 20° flexion (1.73 cm 2 vs 4.00 cm 2 ; p < 0.005). Conclusion: The unstable PFJ is less congruent than the stable PFJ throughout the range of knee movement studied. This approach to mapping PFJ congruency produces a measurable outcome and will allow the assessment of pre- and postoperative results following surgical intervention. This may facilitate the design of new procedures for patients with PFJ instability. If a single axial series is to be obtained on MRI scan, the authors recommend 11° to 20° of tibiofemoral flexion, as this was shown to have the greatest difference in contact surface area between the case and control groups. Cite this article: Bone Joint J 2019;101-B:552–558.